Science-Learning Strengthening Model in Islamic Educational Institution: Case Study at MAN 1 Yogyakarta - Taufik, Opik Abdurrahman; Sumarni, Sumarni; Suprapto, Suprapto (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Advances in science and technology continue to develop and have a broad impact on various aspects of human life, including in the world of education. In order for students to be able to compete in the global world, educational institutions need to strengthen science learning to students. This study aims to explore the advantages of the science-learning strengthening model in Madrasa Aliyah in terms of context, input, process, and output aspects. This study uses a qualitative approach with a qualitative descriptive method. The results of this study indicate that in terms of context, the program for strengthening science learning already exists in the vision and mission of the madrasa, which is to have the advantage of science and technology, which is followed up by madrasa policy to develop KTSP Research and science for local contents and extracurricular activities. From the input side, all were fulfilled except for the laboratory staff who were temporarily carried out by the KIR Trustees. From the process side, science learning strengthening has been carried out well and the output is also quite satisfiying. This can be seen from the score of the National Examination and the number of student achievements, especially in the fields of science and research both in the national and international levels.